Quality of Service Issuance of Trading Business License at the One Door Integrated Service and Investment Department of Medan City - Novrina Sahera Lubis; Simson Ginting (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Quality is the difference between the expectations and the reality of customers for the service they receive. One of the main tasks of the government is to provide services to fulfill the wants and needs of the community. This research describes the quality of service for obtaining issuance of Trading Business License (SIUP) in the Department of Investment and Integrated Services One Door City of Medan. This study is motivated by the impression that the government bureaucracy in providing services is slow. To assist the community in the service process, the Minister of Home Affairs issued Regulation of the Minister of Home Affairs issued a Regulation of the Mayor of Medan No. 69 of 2017 concerning Guidelines for One Door Services so that services can run effectively and prime. The method used in this study is descriptive qualitative, using indicators presented by Zeithaml, et al such as Tangible, Reliability, Responsiveness, Assurance, and Empathy as an indicator to measure how far the results of quality of public service has been done. Quality of public services in the issuance of SIUP in the Department of Investment and Integrated Services One Door city of Medan, can be said to have met the dimensions or any benchmark on the theory that the author uses. Although the implementation has not been maximal, as in the performance of public services in the issuance of SIUP which sometimes the time of issuance is not in accordance with the SOPs that has been set, and slow staff response.